ACCURACY, CLARITY, AND READABILITY (ACR) IN HISTORICAL ROMANCE NOVEL TRANSLATION - Nur Rosita (Humanus: Jurnal Ilmiah Ilmu-ilmu Humaniora, 2018)
Historical novel translation requires an advanced competence of translator in relation with the translation quality: how accurate, clear, and readable the translator tries to deliver the writer’s original message to his/her translation version for the readers. The more accurate, clear, and readable the translator’s version is, the easier comprehension of the text will be. This paper was an outline of descriptive research which has been conducted to analyze the translation quality assessment in translating historical romance novel Taj: A Story of Mughal India into Taj: Tragedi Di Balik Tanda Cinta Abadi by Maria M. Lubis. There were three variables factors used; the two novels as objective factor, the translator as genetic factor, and the raters as affective factor to analyze, compare, rate, and score the translation quality. The sentences, clauses, phrases that consisted Indian cultural terms from the two novels were chosen as the data. From the analysis, it was found that the translation quality of this translated novel is accurate, high clear, and high readable obviously effected by an eligible translator who has high level competence and performance in translating the novel.Keywords: translation, historical romance novel, accuracy, clarity, and readability. KEAKURATAN, KEJELASAN, DAN KETERBACAAN DALAM PENERJEMAHAN NOVEL CINTA BERLATAR SEJARAHAbstractPenerjemahan novel berlatar sejarah membutuhkan penerjemah yang kompeten jika dilihat dari segi penilalian kualitas terjemahan seperti keakuratan, kejelasan, dan keterbacaan. Semakin akurat, jelas, dan terbaca suatu produk terjemahan, hasil terjemahan semakin akan mudah dipahami. Penelitian ini adalah penelitian deskriptif yang mengidentifikasi dan menggambarkan penilaian kualitas penerjemahan. Seberapa akurat, jelas, dan terbaca novel terjemahan Taj: A Story of Mughal India menjadi Taj: Tragedi Di Balik Tanda Cinta Abadi oleh Maria M. Lubis. Ada tiga faktor variabel yang digunakan; kedua novel sebagai faktor objektif, penerjemah sebagai faktor genetik, dan tim penilai sebagai faktor afektif untuk menganalisis, membandingkan, menilai, dan memberi angka kualitas terjemahan. Kalimat, klausa, ungkapan-ungkapan yang terdiri dari istilah budaya India dari kedua novel dipilih sebagai data. Dari analisis tersebut, ditemukan bahwa kualitas terjemahan novel yang diterjemahkan ini akurat, sangat jelas, dan mudah dibaca, yang dipengaruhi oleh kepakaran dan kompetensi kinerja dalam menerjemahkan novel tersebut. Kata kunci: penerjemahan, novel cinta sejarah, keakuratan, kejelasan, dan keterbacaan.